Job satisfaction among muslims academician using islamic work ethics as moderator / Nurfadzilla Mohd Fadzel and Wan Noor Azreen Wan Mohd Nordin - Mohd Fadzel, Nurfadzilla; Wan Mohd Nordin, Wan Noor Azree (2014)
Universities worldwide are aiming to have committed academician in their systems. The satisfied academician can work with better performance, effectively and efficiently compared to unsatisfied academician. As job satisfaction was known to have a profound impact on the staff’s performance, it is important for any organization to understand the factors leading to job satisfaction. The general purpose of this study is to understand the level of job satisfaction and the factors contributing to job satisfaction among Muslims academicians at Universiti Teknologi MARA (UiTM) Sarawak were selected as key respondents. In understanding the academicians job satisfaction several objectives has been derived. These objectives include determining the level of job satisfaction,to investigate the factor that most contribute to job satisfaction among Muslims academician, to determine the relationship between demographic factors and job satisfaction and to determine the effect of Islamic Work Ethics on job satisfaction. Result from this study found that work environment factor was the factors that most affected the job satisfaction among the Muslims academician of UiTM Sarawak. Having a positive atmosphere and good relationship with other academician will increase job satisfaction among Muslims academician in UiTM Samarahan. Other than that, the results revealed that the four factors namely remuneration, facilities and utilities, work environment and workload has a significant relationship toward job satisfaction.In addition, the demographics factors such as gender, marital status and length of service does not affect Muslims academician’s job satisfaction. Though it was found that only 0.8% of job satisfaction is represented by Islamic Work Ethics (IWE), it still can be assumed IWE does affect job satisfaction among the Muslims academician based on significant level. Among the recommendations given by the respondent, it was noted that other factors such as less working hours, smaller number of students in class, high speed internet, fair career development, fair treatment among the academician and etc. also plays a significant role in determining the level of job satisfaction among the Muslims academician.